Sementes de Moringa e pó de Quiabo no Tratamento de Efluente Sanitário - Nogueira, Fabíola Cristina Barros (2012)
The wastewater presents major environmental risk when improperly released into water bodies. However, when the wastewater is treated in accordance with their chemical, physical and biological characteristics it is possible to pourable it without compromising the process of self-purification of water.The use of natural polymers in technological processes distinguished by treatment efficacy and not compromising the characteristics of the chemical sludge generated.The objective of this study was to evaluate the efficacy of the seed of Moringa oleifera Lam as natural coagulant and polymer of okra (Abelmoschus esculentus) as adjuvant flocculation in wastewater and industrial wastewater. The moringa´s seeds shelled and ground were added to the wastewater in the following concentrations: (4.0, 5.0, 6.0, 7.0, 8.0, and 9.0 (g L-1)) and thereafter, at the same concentrations were added 0.5 grams of powdered of okra.Tests for coagulation / flocculation, sedimentation and decantation were carried out in bench through Jar Test. After testing the jars´s device was turned off and the sample remained at rest for a period of 40 minutes. Furthermore, were performed physicochemical analyzes for pH and turbidity for all samples. There were performed DBO205 and DQO tests for the raw wastewater and treated. The experiment was conducted using a completely randomized design (CRD) in a 2x6 factorial design. A total of three (03) repetitions, totaling thirty-six (36) plots. It was found that treatment: moringa together with okra provided better results as the density of the flakes, time of coagulation, sedimentation and significantly decrease in the turbidity. For the effluent treated with moringa and okra, was obtained 84.14% efficiency for DBO205 and 84.54% for DQO. These values are within the parameters of effluent discharges into waters Class II.